2008
DOI: 10.1038/cmi.2008.46
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Chemokine Receptor 4 (CXCR4) and Chemokine Ligand 12 (CXCL12) in Metastasis of Hepatocellular Carcinoma Cells

Abstract: Chemokines are involved in human hepatocellular carcinoma (HCC) carcinogenesis. However, the exact mechanism of chemokines in HCC carcinogenesis remains unknown. Here we investigated the roles of chemokine receptor 4 (CXCR4) and chemokine ligand 12 (CXCL12) in the metastasis of HCC. We found that the expression levels of CXCR4 mRNA in HCC tissues, MHCC97 cells, and HUVEC cells were 2.52 ± 1.13, 2.34 ± 1.16 and 1.63 ± 1.26, respectively and that the CXCR4 protein levels were 1.38 ± 0.13, 1.96 ± 0.32 and 1.86 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 33 publications
4
75
0
2
Order By: Relevance
“…Previous studies have depicted higher expression of CXCL12 and CXCR4 in HCC specimens than the surrounding tissues [78] . It has been demonstrated in different studies that CXCR4 and CXCL12 may play a significant part in HCC metastasis and invasiveness of the tumor [79,80] . A significant correlation was observed between CXCR4 expression, tumor progression, metastasis, and a decreased survival rate [80] .…”
Section: Chemokine Ligand-chemokine Receptor Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have depicted higher expression of CXCL12 and CXCR4 in HCC specimens than the surrounding tissues [78] . It has been demonstrated in different studies that CXCR4 and CXCL12 may play a significant part in HCC metastasis and invasiveness of the tumor [79,80] . A significant correlation was observed between CXCR4 expression, tumor progression, metastasis, and a decreased survival rate [80] .…”
Section: Chemokine Ligand-chemokine Receptor Axismentioning
confidence: 99%
“…It has been demonstrated in different studies that CXCR4 and CXCL12 may play a significant part in HCC metastasis and invasiveness of the tumor [79,80] . A significant correlation was observed between CXCR4 expression, tumor progression, metastasis, and a decreased survival rate [80] . However, the lack of a loss of function mutation of the tumor suppressor gene p53 gene on CXCR4 expression in HCC indicated yet another unidentified mechanism [81] .…”
Section: Chemokine Ligand-chemokine Receptor Axismentioning
confidence: 99%
“…A large body of studies have highlighted that a range of HCC-derived cytokines including chemokine ligand 2 and macrophage colonystimulating factor promote recruitment of peripheral blood monocytes into tumor microenvironment and subsequently differentiation into mature macrophages which are designated as tumor-associated macrophages (TAMs) (Benetti et al, 2008;Zhu et al, 2008;Takai et al, 2009). Furthermore, activated TAMs in turn establish a distinct inflammatory microenvironment responsible for stimulating proliferation, invasion, metastasis and angiogenesis of HCC (Peng et al, 2005;Schimanski et al, 2006;Liu et al, 2008;Kuang et al, 2010;Werno et al, 2010;Chen et al, 2012). It is reasonable to believe that the vicious circle between HCC and TAMs is the driving engine of HCC for its continuous deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, CXCL10 levels correlated both with any tumour size and with transaminase levels suggesting that it could be used as marker of liver inflammation status and cancer progression. CXCL12 is known to play a role both in pathogenesis by promoting tumor growth and malignancy, and in the HCC metastatic network by recruiting endothelial cell tumor progenitors (Liu et al, 2008;Burns et al, 2006;Kryczek et al, 2007). Recently, some papers have suggested that -NGF was involved in cancer growth and metastasis and was detected in diseased liver tissues; in fact this protein has been suggested to be involved in chronic inflammation leading to cancer (Rasi et al, 2007).…”
Section: Evaluation Of Cytokines In Hcc Patients With Hcv-related Cirmentioning
confidence: 99%